Variations in the Translation of the Letter Jar "Min" in the Qur'an and Its Translation into the Palembang Language - M. Adhim Rajasyah; Sutrisno Hadi; Muhammad Arpah Nurhayat (Journal of Islamic Thought and Contemporary Studies, 2025)
This study examines the variations in translating the preposition min in the Qur’an into the Palembang language. The preposition min is one of the most frequently occurring particles in the Qur’an and carries diverse meanings depending on the verse context, namely Ibtida’ Zaman wa Makan (beginning of time and place), Tab‘id (partitive), Bayan lil Jinsi (specification of type), and Badal (substitution). This research employs a library research method with a documentation approach, collecting primary data from the Qur’anic text and its Palembang translation published by the Indonesian Ministry of Religious Affairs in 2019, as well as secondary data from books, journals, and related studies. Data analysis was conducted interactively through data reduction, presentation, and verification to draw conclusions. The results indicate that the translation of min into Palembang not only preserves the accuracy of the Qur’anic meaning but also adapts to the local linguistic structures and cultural norms. The translation variations use appropriate equivalents in Palembang alus (refined language) and seari-ari (everyday language), ensuring effective communication for readers. Moreover, this study emphasizes the importance of linguistic and cultural approaches in Qur’anic translation to convey divine messages accurately, contextually, and meaningfully, while contributing to the preservation of Palembang language and culture. This research is expected to serve as a reference for translators, scholars, and religious education practitioners in developing local translations that remain faithful to the original meaning of the Qur’an.